The Effect of Training Programs on Capacity Building of Posyandu Cadres Through Managerial Competence in the Women's Empowerment, Child Protection Office and the People of Binjai City - Ruri Aswansari; Muhammad Isa Indrawan (International Journal of Society and Law, 2024)
The purpose of this study is to find out and analyze the effect of Training on Knowledge mediated by Managerial Competence in Posyandu Cadres of Employees of the Women's Empowerment, Child Protection and Community Service (DP3AM) of Binjai City. This research was carried out at the Women's Empowerment, Child Protection and Community Protection Office (DP3AM) of Binjai City. The type of research is quantitative associative. The sample in this study was 172 Posyandu Cadres of the Women's Empowerment, Child and Community Protection Office (DP3AM) of Binjai City. The sampling technique in this study uses a random sampling technique from the entire population of 1205 people. The results of the study show that Training has a significant influence on Knowledge as shown by the T-Statistic value of 24,882 > 1.96 and the P Value of 0.000 < 0.05. In the effect of Training on Managerial Competence, data on T-Statistical values were obtained from 4,948 > 1.96 and P-Value values of 0.000 < 0.05 or there was an influence of Training on Managerial Competence. Managerial Competence has a significant effect on Knowledge with a T-Statistic value of 3,039 > 1.96 with a P-Value of 0.000 < 0.05. In the indirect influence, the results show that Managerial Competence has a role as an intervening variable in explaining the relationship between Training and Knowledge of Posyandu Cadres. This shows that improvements in training can improve Managerial Competence, which ultimately contributes to increasing the Knowledge of Posyandu Cadres of the Women's Empowerment, Child and Community Protection Office (DP3AM) of Binjai City.